Adrenal Incidentalomas in Cancer Patients Are Not Always “Innocent”: A Case Report and Review of the Literature - Panagiota Economopoulou; Giannis Mountzios; Ioannis Kotsantis; Marios Bakogeorgos; Vassilios Ramfidis; Ioannis Kapiris; Efstratios Patsouris; Nikolaos Kentepozidis (Case Reports in Medicine)
Herein, we report an unusual case of a 78-year-old woman with synchronous presentation of sigmoid cancer and a nonfunctioning primary adrenal cortex carcinoma, who developed superior vena cava syndrome due to metastatic lymphadenopathy from the latter malignancy. Our case suggests that adrenal incidentalomas during initial staging evaluation after cancer diagnosis are not always “innocent” and should not be “a priori” considered incidental findings attributed to hyperplasia, adenoma or even a non life-threatening metastasis from the primary tumor. It also emphasizes the importance of a continuous assessment of patients with synchronous primary malignancies, in order to timely evaluate changes in clinical or biological behavior and administrate the appropriate treatment.